The ERN1 transcription factor gene is a target of the CCaMK/CYCLOPS complex and controls rhizobial infection in Lotus japonicus. Issue 1 (15th May 2017) - Cerri, Marion R.; Wang, Quanhui; Stolz, Paul; Folgmann, Jessica; Frances, Lisa; Katzer, Katja; Li, Xiaolin; Heckmann, Anne B.; Wang, Trevor L.; Downie, J. Allan; Klingl, Andreas; de Carvalho‐Niebel, Fernanda; et al.
Summary: Bacterial accommodation inside living plant cells is restricted to the nitrogen‐fixing root nodule symbiosis. In many legumes, bacterial uptake is mediated via tubular structures called infection threads (ITs). To identify plant genes required for successful symbiotic infection, we screened an ethyl methanesulfonate mutagenized population of Lotus japonicus for mutants defective in IT formation and cloned the responsible gene, ERN1, encoding an AP2/ERF transcription factor. We performed phenotypic analysis of two independent L. japonicus mutant alleles and investigated the regulation of ERN1 via transactivation and DNA–protein interaction assays. In ern1 mutant roots, nodule primordia formed, but most remained uninfected and bacterial entry via ITs into the root epidermis was abolished. Infected cortical nodule cells contained bacteroids, but transcellular ITs were rarely observed. A subset exhibited localized cell wall degradation and loss of cell integrity associated with bacteroid spread into neighbouring cells and the apoplast. Functional promoter studies revealed that CYCLOPS binds in a sequence‐specific manner to a motif within the ERN1 promoter and in combination with CCaMK positively regulates ERN1 transcription. We conclude that the activation of ERN1 by CCaMK/CYCLOPS complex is an important step controlling IT‐mediated bacterial progression into plant cells.